Kambazithe Makolekole and his valimba group: a glimpse of the technique of the Sena xylophone - Tracey, Andrew (International Library of African Music, 2017)
The valimba xylophone of the Sena people of Malawi has been described by several writers, notably Kubik in his recently published two-record collection "Opeka Nyimbo". This article aims to amplify these descriptions, by discovering what it is that the young virtuoso players are actually doing on their huge xylophone, with its shimmering patterns of sound at breakneck tempo, its sudden repeated notes, and its rich harmonic sequences that are clearly related to those of the Shona in Zimbabwe and then- neighbours in Mozambique and Northern Transvaal, and by providing descriptions of the actual playing technique of the instrument to demonstrate something of its unique style.
Keywords: African Music